Characterizing student engagement across medical universities in Iran: a national qualitative study - Saadati, Mohammad; Sabri, Vahid; Motaarefi, Hossein; Bayrami, Moslem; Karimkhani, Amirreza (Frontiers in Education, 2025)
IntroductionStudent engagement (SE) is an emerging and trending concept in higher education, and it has been defined as a quality measure for medical universities. The aim of this study was to explore student engagement in medical universities in Iran through a national study.MethodsUsing a qualitative phenomenological approach, this study explored student engagement in medical universities in Iran in 2024. Participants were purposively selected from students who were actively involved in the student committee for medical education development at medical universities. An open-ended, goal-driven questionnaire, along with demographic information, was used for data collection. An inductive conventional content analysis method was employed for data analysis using MAXQDA 18. The Lincoln and Guba criteria, including dependability, credibility, transferability, and confirmability, were applied to ensure the rigor of the results.ResultsA total of 48 students participated from 34 medical universities. The mean age of the participants was 22 years. Student engagement was identified as a mutually beneficial strategy for both students and universities. A broad spectrum of activities, including training, curriculum planning, educational evaluation, and governance, were believed to involve students. To overcome the identified barriers to student engagement (SE), such as low incentives for students, lack of a partnership culture, and time restriction, the participants suggested strengthening student agency, encouraging active participation from professors, valuing SE, and promoting fair engagement opportunities.ConclusionStudent engagement in medical universities in Iran is of interest to students, but it faces barriers across various domains. Developing a virtuous and value-based engagement process—through promoting a partnership culture, strengthening student agency, establishing SE strategies in governance, encouraging professors’ mentoring and participation, and truly acknowledging students—will promote SE in medical universities and contribute to the improvement of the learning environment.